2017
DOI: 10.1017/s1478951517000748
|View full text |Cite
|
Sign up to set email alerts
|

“We never speak about death.” Healthcare professionals' views on palliative care for inpatients in Tanzania: A qualitative study

Abstract: Despite the fact that all the HCPs interviewed were regularly involved in providing palliative and EoLC, they had received limited formal training in its provision, although they identified such training as a universal requirement. This training gap is likely to be present across much of SSA. Palliative care training, particularly in terms of communication skills, should be comprehensively integrated within undergraduate and postgraduate education. Research is needed to develop culturally appropriate curricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…A lack of access to medicines and resources was noted as a barrier to providing care in four studies (Q28). 20,47,58,60 Three of these were conducted in low-income countries where medical care access is limited for economic reasons; however, one study was based in the United Kingdom. 60 It was not clear whether the lack of access in this instance was financial or logistical.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…A lack of access to medicines and resources was noted as a barrier to providing care in four studies (Q28). 20,47,58,60 Three of these were conducted in low-income countries where medical care access is limited for economic reasons; however, one study was based in the United Kingdom. 60 It was not clear whether the lack of access in this instance was financial or logistical.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…A large additional literature base was identified in the scoping review that confirms these findings, emphasizing PC preferences relating to the needs of populations ( Harding and Higginson, 2004 ; Barnard, 2006 ; Harding et al , 2008 ; Selman et al , 2009 ; Alsirafy et al , 2010 ; Gysels et al , 2011 ; Harding et al , 2013a ; Powell et al , 2013 ; Powell et al , 2014 ; van Niekerk and Raubenheimer, 2014 ; Selman et al , 2015 ; Luyirika et al , 2016 ; Chisumpa et al , 2017 ; Kimani et al , 2018 ; Lewis et al , 2018 ; Reid et al , 2018 ). Although these do not address the integration of PC specifically, they support PC integration by guiding what type of PC is needed and preferred by a population.…”
Section: Resultsmentioning
confidence: 88%
“…The focus group guides acknowledge the uncertainty of death and the predominant belief in God amongst Tanzanians [ 63 – 65 ]; this was because information gathered from the research nurses and other Tanzanian natives strongly suggested that approaching the topic of death from this perspective would encourage discussion. This is an important limitation of the study, but we felt that this was a culturally appropriate approach to address the issue considering that the topic is taboo in Tanzania [ 10 ]. Even though there was significant variability in our participant sample, especially with the illness diagnoses and the inclusion of allied health professionals, we acknowledge that not involving lay community members limits our understanding of QoD in Moshi.…”
Section: Discussionmentioning
confidence: 99%
“…Expert panel included KCMC’s Palliative Care service, local healthcare providers, and researchers with qualitative research experience. Vignettes were used to help normalize the topic, some of which were adapted from the FG scripts used in Lewis et al’s study, with author permission [ 10 ]. Other noteworthy factors and concepts that influenced the creation of the FG guide include: 1) predominant cultural values that prioritize community over self [ 28 31 ]; 2) the significant role of family in a patient's EoL care [ 10 , 29 ]; and 3) physician reluctance to “break bad news” [ 10 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation